Therapeutic guidelines in chronic low back pain - Daniela Taneva; Angelina Kirkova; Petar Atanasov (Pensoft Publishers, 2021)
Chronic low back pain is a heterogeneous group of disorders with recurrent low back pain over 3 months. The high incidence of lumbago is an important phenomenon in our industrial society. Patients with chronic low back pain often receive multidisciplinary treatment. The bio approach, the psycho-approach, and the social approach optimally reduce the risk of chronicity by providing rehabilitation for patients with persistent pain after the initial acute phase. Damage to the structures of the spinal cord and the occurrence of low back pain as a result of evolutionary, social and medical causes disrupt the rhythm of life and cause less or greater disability. Recovery of patients with low back pain is not limited only to influencing the pain syndrome but requires the implementation of programs to eliminate the complaints that this pathology generates in personal, family and socio-professional terms. This paper aims to familiarize the audience with the medication used, and the programs for active recovery in patients suffering from chronic low back pain.